Associations between childhood maltreatment and behavioral sleep disturbances across the lifespan: A systematic review. (August 2022) - Brown, Samantha M.; Rodriguez, Kerri E.; Smith, Amy D.; Ricker, Ashley; Williamson, Ariel A.
Summary: Childhood maltreatment has a range of long-term developmental and health consequences. Emerging research suggests that sleep disturbances may be a key behavioral health risk factor implicated in the relationship between maltreatment and poor health across the lifespan. This systematic review examined the association between maltreatment and behavioral sleep disturbances in childhood and adulthood. Studies were identified through PsycINFO, PubMed, and alternative search strategies such as Google Scholar and reference list checks, with an end date of July 2021. Quantitative, peer-reviewed articles examining behavioral sleep outcomes and/or characteristics among maltreatment-exposed samples were included. We assessed the potential risk of bias by examining study design and sleep and maltreatment assessment methods. Across 73 studies included in this review, there was a robust association between childhood maltreatment and behavioral sleep disturbances. Findings suggest that linkages between maltreatment and sleep outcomes diverge with respect to maltreatment characteristics, type of behavioral sleep disturbance assessed, use of subjective versus objective measures, and study design. Given that behavioral sleep disturbances are modifiable, more research is needed that incorporates objective measures of sleep and longitudinal designs to identify specific points of intervention to mitigate the potential long-term impacts of childhood maltreatment on health across socio-demographically diverse populations.